Rate of perihaematomal oedema expansion is associated with poor clinical outcomes in intracerebral haemorrhage. Issue 11 (27th July 2016) - Murthy, Santosh B; Urday, Sebastian; Beslow, Lauren A; Dawson, Jesse; Lees, Kennedy; Kimberly, W Taylor; Iadecola, Costantino; Kamel, Hooman; Hanley, Daniel F; Sheth, Kevin N; Ziai, Wendy C
Abstract : Background: Perihaematomal edema (PHE) expansion rate may be a predictor of outcome after intracerebral haemorrhage (ICH). We determined whether PHE expansion rate in the first 72 hours after ICH predicts outcome, and how it compares against other PHE measures. Methods: We included patients from the Virtual International Stroke Trials Archive. We calculated PHE expansion rate using the equation: (PHE at 72 hours PHE at baseline)/(time to 72-hour CT scan time to baseline CT scan). Outcomes of interest were mortality and poor 90-day outcome (modified Rankin Scale score of ≥3). Logistic regression was used to assess relationships with outcome. Results: A total of 596 patients with ICH were included. At baseline, median haematoma volume was 15.0 mL (IQR 7.9–29.2) with median PHE volume of 8.7 mL (IQR 4.5–15.5). Median PHE expansion rate was 0.31 mL/hour (IQR 0.12–0.55). The odds of mortality were greater with increasing PHE expansion rate (OR 2.63, CI 1.10 to 6.25), while the odds of poor outcome also increased with greater PHE growth (OR 1.67, CI 1.28 to 2.39). Female sex had an inverse relationship with PHE growth, but baseline haematoma volume had a direct correlation. Among other PHE measures, only interval increase in PHE correlated with poor outcome. There was no significant difference between the 2 measures of PHE volume expansion. Conclusions: Rate of PHE growth over 72 hours was an independent predictor of mortality and poor functional outcomes following ICH. Baseline haematoma volume and gender appear to influence PHE growth.